Promotional effect of HZSM-5 on the catalytic oxidation of toluene over MnOx/HZSM-5 catalysts. Issue 12 (3rd February 2016) - Huang, He; Zhang, Chuanhui; Wang, Lei; Li, Genqin; Song, Liang; Li, Guangci; Tang, Sifu; Li, Xuebing
Abstract : The cooperative action between the redox ability of MnO x layer and the acidity properties of the HZSM-5 zeolite over MnO x /HZSM-5 catalysts significantly promotes the catalytic oxidation of toluene. Abstract : A series of HZSM-5 supported MnO x catalysts with different manganese contents were prepared by an incipient impregnation method and tested for the catalytic oxidation of toluene. The catalytic results indicate that 10% MnO x /HZSM-5 exhibits the optimum catalytic activity, excellent catalytic durability in dry conditions and high regeneration capability in humid conditions. The dispersion of MnO x species on the HZSM-5 surface significantly reduces coke formation and simultaneously efficiently accelerates the oxidative decomposition of coke deposition during toluene catalytic oxidation. An obvious cooperative action is present on the MnO x /HZSM-5 catalysts for the catalytic oxidation of toluene, which is originally attributed to the excellent toluene adsorption capacity and trapping ability of HZSM-5 as well as the superior redox ability of the MnO x species. The correlation between characterizations and the catalytic results reveals that the mesoporous structure and low-temperature reducibility of MnO x are key factors responsible for the catalytic performance of toluene oxidation. Moreover, the Brønsted acid sites of the HZSM-5 zeolite, as active promoters, play a significant role in the catalytic oxidation of toluene through a comparative analysis with SiO2 and Al2 O3 supported MnO x catalysts. The existence of a cooperative action between the redox ability of the MnO x species and the acidic properties of the HZSM-5 zeolite in the MnO x /HZSM-5 catalysts results in a high catalytic activity for the reaction.